Response to Rituximab in a Case of Lupus Associated Digital Ischemia - Orhan Küçükşahin; Nurşen Düzgün; Alexis K. Okoh; Emre Kulahçioglu (Case Reports in Rheumatology)
We report the case of a 38-year-old female patient with systemic lupus erythematosus (SLE) and Jaccoud arthritis (JA) that sequentially developed digital ischemic lesions of the hands. In spite of follow-up treatment with glucocorticoids, immunosuppressant, antiaggregant, and potent vasodilatator agents, a serious progression to digital gangrene over a one-month period was observed. Surprisingly, her nonhealing digital lesions improved after two cycles of rituximab (RTX) administration.